Dinamika Integrasi Nilai-Nilai Sedulur Sikep Samin dalam Pembelajaran PAI untuk Membangun Multiple Character Peserta Didik di Sekolah Dasar - Yeri Utami; Rina Murtyaningsih; Sholihul Anwar; Widodo; Armando Dos S. Lopes5 (CV. Creative Tugu Pena, 2026)
This study aims to examine the dynamics of integrating Sedulur Sikep Samin values into PAI learning to develop students’ multiple character at SD Muhammadiyah Blora. This research employs a transcendental phenomenological approach following Moustakas, involving eight participants: a school principal, two PAI teachers, three students, and two parents. Data were collected through semi-structured in-depth interviews, participant observation, and document analysis. Data analysis followed Moustakas’ four stages: epoché (bracketing), phenomenological reduction (horizonalization and clustering), imaginative variation, and synthesis to identify the essence of participants’ experiences in integrating values into multidimensional character formation. The findings reveal five key dynamics in the integration process: (1) value harmonization between Samin philosophy and Islamic teachings through the convergence of universal principles; (2) pedagogical adaptation incorporating storytelling, experiential learning, and value reflection; (3) collaboration among the three centers of education (school, family, and community); (4) transformation through the hidden curriculum to strengthen value internalization; and (5) holistic character assessment through authentic behavioral observation. The results indicate significant improvement in five character dimensions: tolerance, honesty, simplicity, mutual cooperation, and spirituality.